Physical and excess properties for binary systems containing an alcohol and ionic liquid at T = 298.15 K - Eugénia A. Macedo (2012)
The density, speed of sound, and refractive index for binary systems containing ethanol, or 1-propanol, or 2-propanol mixed with the ionic liquids 1-butyl-3-methylpyridinium bis(trifluoromethylsulfonyl)imide or 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide were measured at 298.15 K and 1 atm. From the experimental data, excess molar volumes (VE), excess molar isentropic compressibility (KS,m/E), and excess refractive index (nD/E) were calculated and fitted using a Redlich-Kister type equation. The VE for the studied systems presented asymmetrical curves that changed sign along the composition range, which were quite common in mixtures containing two components with a large molar volume difference. The values of VE showed a maximum at low concentrations of alcohol and a minimum around x1 = 0.9, which became more negative as the chain length of the alcohol decreased. The studied systems showed negative KS,m/E values in the whole composition range. The binary system containing ethanol presented a minimum at x1 0.8, while the other two systems showed a minimum at x1 0.7. nD/E curves were also asymmetrical showing a minimum at low concentrations of alcohol and a maximum at high molar fractions of alcohol. This is an abstract of a paper presented at the CHISA 2012 - 20th International Congress of Chemical and Process Engineering and PRES 2012 - 15th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (Prague, Czech Republic 8/25-29/2012).